(untitled) (Research, Society and Development, 2020)
In this work, a study was carried out on the water quality of a well and a cistern in the region of Campina Grande-PB. The collected samples were sent to the Water and Effluent Quality Control Laboratory at SENAI-CTCC Albano Franco. Physical-chemical analyzes were performed, pH, turbidity, color, free residual chlorine, total hardness, chloride, and total dissolved solids were determined. The classification of water potability was based on the physical-chemical parameters of ordinance 2,914 of December 2011, from the Ministry of Health, where the results obtained indicated that the samples were not fit for human consumption. The objective was to evaluate and compare the physical-chemical parameters of water samples from a well and a cistern located in the city of Campina Grande, Paraíba, such as: pH, turbidity, color, free chlorine, chlorides, total hardness and dissolved solids totals, characterizing our study as quanti-qualitative.